The Impact of Divorce on Psychological, Emotional and Mental Children in the Perspective of Islamic Law - Syarif, Muhammad; Zulhamdi, Zulhamdi (Syarah: Jurnal Hukum Islam dan Ekonomi, 2023)
Every human being certainly has the hope of building a family which is the goal of marriage law, namely building a family that is sakinah, mawaddah wa rahmah. However, there are various factors that cause damage and destruction of a household so that they choose to divorce. The result of the divorce will damage the relationship between husband and wife and have an impact on the psychological, emotional and mental health of children. Data collection with a library research approach, which is carried out by searching for research data or information through reading scientific journals, reference books and publication materials available in various sources. The results of this study indicate that married couples sometimes have to face problems in their household life, the emergence of problems in the household can be caused by many things including economic factors, lack of a sense of responsibility, differences in outlook on life that can lead to household crises. The woman who will become a widow does not think about other people's views on her because she thinks this is her life and she is the one who lives it all, it's just that there is guilt in her child when she has to divorce. Of course, there is an impact of divorce that will arise on the psychological development of their children, trying so that their children do not lose the love of a father.